Ternary pseudorandom signal design for uniform excitation and reduced effect of nonlinear distortion - Tan, A.H.; Foo, M.F.L. (2006)
Ternary pseudorandom signals with uniform spectra are useful for system identification, particularly during prototyping when actuators are rather primitive. To reduce the effect of nonlinear distortion on the linear estimate, the signal should have harmonic multiples of two and three suppressed. No analytical method is currently available for the design of such signals, while optimisation cannot guarantee an optimal solution. An analytical method that guarantees optimality is introduced in which the pseudorandom signal, generated from a Galois field, is designed based on a primitive version of the signal having suitable harmonic properties and a sparse spectrum with multiple periodicity.